Screening of ligands for the Ullmann synthesis of electron-rich diaryl ethers - Otto, Nicola; Opatz, Till (Beilstein Journal of Organic Chemistry, 2012)
In the search for new ligands for the Ullmann diaryl ether synthesis, permitting the coupling of electron-rich aryl bromides at relatively low temperatures, 56 structurally diverse multidentate ligands were screened in a model system that uses copper iodide in acetonitrile with potassium phosphate as the base. The ligands differed largely in their performance, but no privileged structural class could be identified.
Keywords: catalysis; C–O bond formation; diaryl ethers; nucleophilic aromatic substitution; Ullmann-type coupling